1995
DOI: 10.1097/00005392-199502000-00065
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Growth After Successful Varicocele Correction in Adolescents: Comparison of Artery Sparing Techniques With the Palomo Procedure

Abstract: Testicular growth after varicocele surgery was evaluated in 116 boys 9 to 20 years old. A total of 88 boys was available for followup testicular examination 3 to 60 months after successful varicocele repair (mean 25). Left testicular volume loss of 2 cc or greater was present preoperatively in 72 of the 88 patients. The Palomo procedure was performed in 36 cases and repair using artery sparing techniques was done in 36. Mean relative left testicular volume increased 18% in the artery sparing group and 21% in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 9 publications
2
40
0
2
Order By: Relevance
“…This led those authors to recommend the Palomo mass ligation as the procedure of choice. Atassi et al [28] later reported a 1.3% persistence rate with total ligation in this group. Thus we consider that the term 'recurrence' more correctly describes a varicocele which is not present 3-6 months after surgery and develops sometime thereafter.…”
Section: Discussionmentioning
confidence: 54%
“…This led those authors to recommend the Palomo mass ligation as the procedure of choice. Atassi et al [28] later reported a 1.3% persistence rate with total ligation in this group. Thus we consider that the term 'recurrence' more correctly describes a varicocele which is not present 3-6 months after surgery and develops sometime thereafter.…”
Section: Discussionmentioning
confidence: 54%
“…However, several studies have evaluated spermatic artery ligation and found no physiological detriment to the testis. Atassi et al [14] compared testis growth after the Palomo procedure vs the artery-sparing technique, and noted comparable compensatory growth in both groups, with no evidence of atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…The median (range) age at surgery was 15 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) years. Patients were stratified based on the surgical technique…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deux arguments majeurs sont en faveur de cette indication de la chirurgie chez l'adolescent, d'une part la r6cup6ration de la croissance testiculaire apr6s cure du varicoc61e [13], d'autre part le fait que les r6sul-tats de la chirurgie sur la fertilit6 semblent meilleurs lorsque le traitement est r6alis6 pr6cocement [14].…”
Section: Traitement Du Varicoceleunclassified